Early-Onset Neonatal Sepsis and Antibiotic Use in Northeast Thailand - Kiatchoosakun, Pakaphan; Jirapradittha, Junya; Sirikarn, Prapassara; Laopaiboon, Malinee; Pattanittum, Porjai; Chandrakachorn, Woranart; Srirojana, Sakulrat; Jeffery, Heather; Green, Sally; Lumbiganon, Pagakrong; on behalf of the SEA-URCHIN Study Group (American Journal of Perinatology, 2019)
Objective Antibiotics are commonly prescribed in neonatal intensive care units (NICUs) for suspected sepsis because of the nonspecific clinical symptoms of sepsis. The overuse of antibiotic is associated with adverse outcomes. This study aimed to determine the rate of early-onset sepsis (EOS) and antibiotic use in neonates admitted to three NICUs in Northeast ThailandStudy Design This is a descriptive study using the data collected in the South East Asia—Using Research for Change in Hospital-acquired Infection in Neonates project. Neonates admitted within 3 days of life were included. EOS was defined as neonates who presented with three or more clinical signs or laboratory results suggested sepsis and received antibiotics for at least 5 days. Those with positive blood culture were culture-proven EOS. Antibiotic use within 3 days of life and up to 28 days was described.Results Among 1,897 neonates, 160 cases were classified as EOS (8.4%) with culture-proven EOS in 4 cases (0.2%). The median durations of antibiotic use in culture-proven and culture-negative EOSs were 15 and 8 days, respectively.Conclusion The rate of culture-proven EOS was low, but there was a high rate of antibiotic use. Antibiotic stewardship should be emphasized.
Keywords: early-onset sepsis; neonate; antibiotic use; Thailand